Changes in calcium channel proteins according to magnesium sulfate administration in placentas from pregnancies with pre-eclampsia or fetal growth restriction. (9th November 2018) - Cha, Hyun-Hwa; Hwang, Jae-Ryoung; Sung, Ji Hee; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae
Abstract : We aimed to evaluate the changes in plasma membrane Ca 2+ -ATPase (PMCA) and sarcoendoplasmic reticulum CA 2+ -ATPase (SERCA-2) according to the antepartal magnesium sulfate (MgSO4 ) administration in the placentas from pregnancies with pre-eclampsia (PE) or fetal growth restriction (FGR). Pregnant women were classified as follows: (group 1) pregnancies without PE or FGR (n=16), (group 2) pregnancies with PE or FGR but without MgSO4 administration (n=14), and (group 3) pregnancies with PE or FGR and with MgSO4 administration (n=28). We observed the localization of PMCA and SERCA-2 in placentas and compared its expression among 3 groups. And we observed its expression in BeWo cells following treatment with MgSO4 and CoCl2 . PMCA staining was more observed in the basal membrane, whereas SERCA-2 staining was observed predominantly under the microvillous membrane. SERCA-2 expression was significantly increased in group 3 compared with that in group 1. Considering the gestational age at delivery, PMCA expression was increased in group 2 and group 3 compared with that in group 1 after 36 weeks of gestation. SERCA-2 was increased in group 3, but not in group 2 compared with that in group 1 after 36 weeks of gestation. In BeWo cells, MgSO4 treatment increased PMCA and SERCA-2 expression. PMCA expression was influenced by gestational age at delivery, and SERCA-2 expression was increased in the presence of PE and antepartal MgSO4 administration. This indicates that antepartal MgSO4 administration has a greater influence on SERCA-2 than PMCA.